Monitoramento de mosca-das-frutas em áreas produtoras de mamão (Carica papaya l.) no Município de Baraúna, RN - Davi, Mateus Caetano Costa (Universidade Federal Rural do Semi-Árido, 2018)
One of the main crops in the Brazilian fruit production, the papaya (Carica papaya L.) is constantly attacked by pests and diseases. Within pests, the fruit fly is the one that brings one of the greatest economic impact, causing fruit depreciation and impeding exportation, when considering the phytosanitary barriers proposed in the IN nº 5 (Normative Instruction #5) dated from January 22nd of 2008, which presents all criteria for exportation to the USA and other countries. To keep this agribusiness running, the monitoring of producing areas must be continuous. The Ceratitis capitata (Wiedemann), known as the Mediterranean fruit fly, was assessed through surveys held between July 2016 and December 2017, following the population level, new fruit fly species that possibly may be in these areas, population fluctuation, and the FTP index (Fly per trap per day). Traps were collected weekly in two different Carica papaya L.-producing areas in the city of Baraúna-RN. McPhail and Jacksontype traps were used to collect the specimens. Jackson traps were more efficient in catching C. capitata. A total of 1080 specimens were collected throughout the experiment period, all of them collected in Jackson-type trap. Out of the monitored areas, none has presented an FTP index average within the limits allowed for exportation, since it would be necessary to maintain below the 1-point for 12 months. Results show a variation in population within the assessed months, with a more significant specimens capture in 2016.
Monografia
Keywords: Fruticultura; Índice MAD; C. capitata; Fruit produciton; FTP index; Anastrepha spp; C. capitata; Anastrepha spp; CIENCIAS AGRARIAS::AGRONOMIA